Balampah dalam Budaya Banjar (Konsep, Filosofi, Identitas dan Nilai-Nilai Pendidikan Islam) - Sinta Masitha; Ali Mu’ammar Zainal Abidin (CV. ITTC INDONESIA, 2026)
Indonesia is rich in ethnic and cultural diversity, with each local culture representing a collection of knowledge, values, norms, and shared practices. Among these, the Banjar culture in South Kalimantan exemplifies a long history of acculturation influenced by indigenous beliefs, Hindu-Buddhist traditions, and Islam. One notable example is the Balampah tradition, a ritual practice originally rooted in local and Hindu-Buddhist beliefs, which has been transformed through Islamic teachings while maintaining its cultural identity. This study aims to analyze the acculturation process in Banjar culture, focusing on Balampah, and to explore how Islamic values influence its transformation. The research employs a library research approach, reviewing books, scholarly articles, historical manuscripts, and documents on Banjar culture, ritual practices, and religious integration. Findings indicate that Balampah functions as a form of spiritual retreat, combining ascetic practices, prayers, and ritual activities aimed at personal purification, protection, and social well-being. The tradition embodies key Islamic educational values, including tauhid (monotheism), tazkiyatun nafs (self-purification), moral and ethical development, and social responsibility. The study demonstrates that Balampah exemplifies a dynamic process of cultural adaptation where local traditions harmonize with Islamic teachings, preserving both religious and cultural identities in contemporary Banjar society.